Kegiatan Pembagian Takjil dalam Upaya Mempererat Tali Persaudaraan di Desa Pucang Buduran, Sidoarjo - Nadzirah Shava Salsabila (Lembaga Pengembangan Kinerja Dosen, 2026)
The distribution of takjil in Pucang Village, Buduran, Sidoarjo a tradition of sharing food to break the fast is not only viewed as a form of individual worship but also plays a vital role in strengthening social bonds among residents. In addition to fostering brotherhood, the practice of sharing takjil also serves as a means of instilling social values such as empathy, mutual cooperation, and a sense of responsibility toward the surrounding community. In the context of the takjil-sharing activity, social solidarity is key to strengthening bonds of brotherhood. In the social life of Muslim communities in Indonesia, the tradition of sharing takjil during Ramadan is not merely a routine distribution of food for breaking the fast, but a social practice that can strengthen the sense of brotherhood among residents. This study employs the Participatory Action Research (PAR) method, an approach that positions the community as both the subject and an active partner throughout the entire research and community service process. The primary purpose of the iftar-sharing activities during Ramadan is not merely to meet the practical needs of breaking the fast, but also to strengthen social bonds and brotherhood among community members through shared experiences and direct interaction.